Faktor Determinan Preferensi dan Perilaku Konsumsi Teh Hitam dan Hijau - Aditya Nugraha; Ujang Sumarwan; Megawati Simanjuntak (Jurnal Manajemen & Agribisnis, 2017)
The objectives of this study were: 1) to analyze the preference, attitude, and consumer behavior toward black and green tea; 2) to analyze the beverage choice factor and its impact on consumer preference on black and green tea; 3) to analyze the impact of consumer attitudes on consumer preference of black and green tea; and 4) to analyze the impact of consumer preference on black and green tea consumption behavior. This research employed a descriptive approach. The data were gathered using online survey method toward 131 respondents with a requirement of consuming black tea and green tea within the last three months. The data were analyzed with the Partial Least Square analysis using SmartPLS program and Fishbein Multi-Attribute. The result of this study showed that the primary benefit felt by the respondents was that the tea was quenching thirsty and serving freshness. The beverage choice factor had a significant effect on consumer preference while the attitude had no effects on consumer preference. In addition, the consumer preference had a significant effect on purchasing behavior of the green and black tea. The product development which should be performed includes taste and flavor innovation that can offer a benefit of quenching thirsty and serving freshness.Keywords: attitude, beverage choice factor, preference, purchasing behavior, tea